Islamic Education According To Imam Ghazali - Muhammad Khairil Mustofa (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2016)
Education has principles place it upright in the material, interaction, innovation and ideals. As with any medicine, engineering or agriculture, respectively can not stand alone but rather a means by which practiced a number of science are closely related to each other and intertwined copy. Islam has a number of characteristics extracted from the Quran and the Sunnah of the Prophet Muhammad, as a source of Islamic teachings. Among the contents of Islamic education that is education of faith, amaliah education, scientific education, moral education and social education. Among one of the leaders of Islamic education was Abu Hamid Muhammad ibn Muhammad Al-Ghazali, he has thought with regard to aspects relating to education, namely the aspect of educational goals, curricula, methods, ethics teacher and student ethics. Turns education according to Imam Al-Ghazali remains actual until now to prove the Law on National Education System (Education) Chapter II, Article 3: